Faktor-Faktor Penentu Persistensi Laba - Warseno, Warseno; Dharmendra, Dharmendra; Susmita Handayani (LPPM UBP, 2022)
The Earnings quality is part of a measure to assess the performance of an entity and then as a consideration for investors to invest, where the quality of report information can be determined by the persistence of earnings. This study aims to examine the effect of operating cash flow, book tax differences (permanent and temporary), debt and firm size on earnings persistence. The population used is the Basic Industry and Chemical sector which is listed on the Indonesia Stock Exchange (IDX). Based on the purposive sampling method, the sample found 11 companies with observations during the 2015-2018 period. The analysis technique used is multiple regression analysis with the help of SPSS 25. The results of this study are operating cash flows, and the amount of debt partially have an impact on earnings persistence. In contrast, the scale of the company, the permanent difference does not affect the persistence of earnings.